2022
DOI: 10.3389/fimmu.2022.930532
|View full text |Cite
|
Sign up to set email alerts
|

A Novel MicroRNA and the Target Gene TAB2 Can Regulate the Process of Sucking Blood in and the Spawn Rate of Hyalomma asiaticum (Acari: Ixodidae) Ticks

Abstract: Ticks are blood-sucking parasites that are harmful to humans and animals. MicroRNAs are a class of conserved small noncoding RNAs that play regulatory roles in the expression of many genes at the posttranscriptional level. Here, a novel miRNA (nov-miR-17) was identified from a small RNA data library of Hyalomma asiaticum by next-generation sequencing. PCR was used to obtain precursor nov-miR-17 by RACE using mature loop primers. The secondary structure was predicted with UNAFold. The interaction of nov-miR-17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Differential expression is an important piece of information to consider when analyzing differences in the expression of factors in different treatment groups. In this study, miRNAs were predicted from sRNAs using rules established for miRNA identification [10], and the candidate miRNAs were compared between all species in the miRBase database (https://mirbase.org, accessed on 5 March 2023). After comparison and analysis, the miR-NAs of tick origin were ultimately identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential expression is an important piece of information to consider when analyzing differences in the expression of factors in different treatment groups. In this study, miRNAs were predicted from sRNAs using rules established for miRNA identification [10], and the candidate miRNAs were compared between all species in the miRBase database (https://mirbase.org, accessed on 5 March 2023). After comparison and analysis, the miR-NAs of tick origin were ultimately identified.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of endogenous noncoding small RNAs of approximately 18–22 nt. A microRNA can exert its functions, such as cell development, immune response, and disease occurrence, by binding to the 3′-UTR or 5′-UTR of target genes (mRNAs) at the posttranscriptional level [ 10 , 11 , 12 , 13 , 14 ]. The main reason is that mRNAs play an important role in the pathogenesis of T. orientalis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of length analysis can be used as an important basis for determining the reliability of sequencing data and can indirectly reflect the characteristics of the distribution of different kinds of small RNAs. These results provide an important reference for data analysis and useful information for the physiological functions of ticks analyzed based on the spatiotemporal expression patterns of small RNAs [ 8 ]. In our study, miRNAs accounted for a large proportion of the 18,162,337, 8,090,736, and 11,807,326 sequences acquired from different developmental stages, indicating that miRNAs have an important function in regulating the posttranscriptional expression level of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Affected by enzyme digestion, the 5′ and 3′ ends of miRNA are mainly uracil (U), and the middle of the sequence is mainly adenine (A). Mature miRNAs show high similarity in different species, especially with regard to the base at positions 2–8, which is absolutely conserved in the same miRNA molecule [ 8 ]. This region is called the “seed region”, which can be divided into the (a) region and (b) region.…”
Section: Introductionmentioning
confidence: 99%
“…RNAi also plays an important role in the efficiency of blood‐sucking processes in ticks. Luo et al (2022) identified a new miRNA (nov‐miR‐17) in Hyalomma asiaticum , which plays an important role in the blood suction process and rate of female's fertility by targeting the TAB2 gene. The overexpression of nov‐miR‐17 indicated that this miRNA affected the engorged weight ( p < 0.001) and spawn rate ( p < 0.001) of female ticks.…”
Section: Domain Of the Reviewmentioning
confidence: 99%